Integrated Assessment of Carbon Capture and Storage (CCS) in South Africa’s Power Sector - Peter Viebahn; Daniel Vallentin; Samuel Höller (Energies, 2015)
This article presents an integrated assessment conducted in order to explore whether carbon capture and storage (CCS) could be a viable technological option for significantly reducing future CO2 emissions in South Africa. The methodological approach covers a commercial availability analysis, an analysis of the long-term usable CO2 storage potential (based on storage capacity assessment, energy scenario analysis and source-sink matching), an economic and ecological assessment and a stakeholder analysis. The findings show, that a reliable storage capacity assessment is needed, since only rough figures concerning the effective capacity currently exist. Further constraints on the fast deployment of CCS may be the delayed commercial availability of CCS, significant barriers to increasing the economic viability of CCS, an expected net maximum reduction rate of the power plant’s greenhouse gas emissions of 67%–72%, an increase in other environmental and social impacts, and low public awareness of CCS. One precondition for opting for CCS would be to find robust solutions to these constraints, taking into account that CCS could potentially conflict with other important policy objectives, such as affordable electricity rates to give the whole population access to electricity.